2014
DOI: 10.1155/2014/560746
|View full text |Cite
|
Sign up to set email alerts
|

Severe Symptomatic Hypermagnesemia Associated with Over-the-Counter Laxatives in a Patient with Renal Failure and Sigmoid Volvulus

Abstract: Hypermagnesemia is an uncommon but a potentially serious clinical condition. Over-the-counter magnesium containing products are widely used as antacids or laxatives. Although generally well tolerated in patients with normal renal function, their unsupervised use in the elderly can result in severe symptomatic hypermagnesemia, especially in those patients with concomitant renal failure and bowel disorders. We report a case of severe symptomatic hypermagnesemia associated with over-the-counter laxatives in a 70-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
(5 reference statements)
0
14
0
3
Order By: Relevance
“…According to a case report in the USA, and South Korea, and two case reports in Japan, all patients had some degree of bowel disorder and all took magnesium-containing laxatives. 11,[17][18][19] In these cases, hypermagnesemia had an iatrogenic cause. Constipation is a common health problem in older adults.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to a case report in the USA, and South Korea, and two case reports in Japan, all patients had some degree of bowel disorder and all took magnesium-containing laxatives. 11,[17][18][19] In these cases, hypermagnesemia had an iatrogenic cause. Constipation is a common health problem in older adults.…”
Section: Discussionmentioning
confidence: 96%
“…There are several reports on the correlation between intake of magnesium‐containing laxatives and symptomatic hypermagnesemia worldwide. According to a case report in the USA, and South Korea, and two case reports in Japan, all patients had some degree of bowel disorder and all took magnesium‐containing laxatives . In these cases, hypermagnesemia had an iatrogenic cause.…”
Section: Discussionmentioning
confidence: 99%
“…High CKD, greater age, and long-term use of magnesium oxide were shown to be risk factors for hypermagnesemia. (3,(5)(6)(7)(8)(9)(10) Most of these studies, however, were case reports or studies of certain groups, including elderly patients, children, and patients undergoing hemodialysis. The results of the present retrospective cohort study showed that reduced renal function was the most important risk factor for hypermagnesemia and high serum magnesium concentration in patients taking magnesium oxide for functional constipation.…”
Section: Discussionmentioning
confidence: 99%
“…(4)(5)(6)(7)(8)(9) Serum magnesium concentrations >5.0 mg/dl have been associated with nausea, headache, light-headedness, and cutaneous flushing, whereas levels above 12 mg/dl have been associated with respiratory failure, complete heart blockage, and cardiac arrest. (10) Recently, the Japanese Ministry of Health, Labour and Welfare recommended that serum magnesium concentrations be measured periodically in geriatric patients and in patients administered magnesium oxide for prolonged periods of time (http://www.pmda. go.jp/files/000219708.pdf).…”
mentioning
confidence: 99%
“…In der Humanmedizin finden sich einige Fallberichte zu einer Hypermagnesiämie aufgrund iatrogener parenteraler Überdosierung sowie oraler Gabe von Antazida, magnesiumhaltigen Ab-führmitteln und Durchführung magnesiumhaltiger Einläufe (16,47,53).…”
Section: Hypermagnesiämie Ursachen Einer Hypermagnesiämieunclassified